Teacher Assistants in the General Education Classroom - Aljohani, Badriah (My University, 2019)
The primary goal of special education is to help students with individualized needs to thrive and find success in the school environment. Research evidence from over the last 30 years in education has consistently demonstrated that students who are mainstreamed, or who are allowed to attend the general classroom with their peers, are more successful. However, there currently is not an infrastructure for supporting these students in the Saudi classroom. This is why increased implementation of professionals and teacher aides are critical to the realization of Saudi Arabia's goals, as they relate to education. Paraprofessionals are an important part of the team that works to help students with special needs achieve success, and they are uniquely qualified to ensure that learners' individual needs are met as they work toward the primary objectives in the general classroom. The current study will consider the best way to increase the number of teacher aides in the system.